Vozes de Stella: Leitura. Escritura. Poesia - Alves, Nathaly Felipe Ferreira (2017)
The aim of this study is to analyse the relations between reading and writing processes in the metapoetic exercise appropriation of modernist expression poems of Brazilian Literature, in the poems that compose ―Reamanhecer‖, second part of Stella Leonardos‘ poetry book Amanhecência (1974). This metapoetic rewriting operates by means of an analogical thinking, in which the figure of the ―critical poet‖ in his relationship with tradition is outlined. By this double movement, founded on the relocation of the lyrical subject ―out of itself‖, this research hypothesis arises on a singular ―book-anthology‖ in which the poet seizes the poems which she dialogues with, based on two procedures: the ―expansion‖, generator of the ―parallel song‖, and the ―reduction‖, in which the gloss of the epigraphs is a key resource – both on the bases of the metapoetic perspective. The theoretical foundations for the analysis are arised on the studies of Eliot (1989) and Maciel (1999) on the field of ―critical poetry‖; Valéry (2007), Blanchot (1987; 2013) and Badiou (2002) regarding to the status of poetic thinking; in addition to Collot (2004) on the ―lyrical subject out of itself‖. The methodology of analysis of the corpus – six poems of ―Reamanhecer‖ (“Qualquer coisa chora pelo mar aberto”, “Paulistana”, “Soneto de ar amigo”, “Da bomba”, “Do antológico bêbedo” and “Soneto alado‖), which dealings with poems of Ribeiro Couto, Oswald de Andrade, Mário de Andrade, Carlos Drummond de Andrade, Dante Milano e Jorge de Lima, respectively – focused on the comparative analysis perspective of the poems. It is concluded that Stella Leonardos creates a singular ―history of literature written in verse‖ which determines not only a new concept of poetic-critical anthology, revitalizing a synchronic history of Brazilian Literature, as proposed by Haroldo de Campos (1969), but also envisages an instigating metapoetic exercise in the formation of the literary reader